2013
DOI: 10.1590/s0103-90162013000300003
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of conventional agrochemicals used in rice crops with the entomopathogenic fungus Metarhizium anisopliae

Abstract: The toxicological impact of chemical pesticides on fungal entomopathogens and their use in tank-mixing can be directly measured through in vitro compatibility tests. This study reports the in vitro toxicity of eight insecticides, four fungicides and five herbicides in the conidial germination, vegetative growth and conidiation of Metarhizium anisopliae (strain CG 168). A conidial suspension containing the pesticide at recommended field dosage was subjected to constant agitation in a rotary shaker for 3h to sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 24 publications
1
26
0
2
Order By: Relevance
“…For the compatibility assessments of each copper fungicide with B. bassiana , the Biological Index (BI) was calculated. This index classifies chemical compounds according to their toxic effects on fungi cultured in vitro on a solid‐poisoned medium (Silva, Quintela, Mascarin, Barrigossi, & Lião, ). The BIs were calculated using the B. bassiana colony mean vegetative growth (VG), sporulation (SP) and conidia germination (GR) percentages, as compared with the controls (Soares, Monteiro, Babosa, & Mochi, ), as follows:BI=47VG+43SP+10GR100where the BI defines the level of fungicide toxicity against the entomopathogenic fungus ( B. bassiana ) in vitro, and GR, VG and SP are the proportions of conidia germination, fungus vegetative growth and conidia numbers, respectively, of the fungicide treatments compared with the controls.…”
Section: Methodsmentioning
confidence: 99%
“…For the compatibility assessments of each copper fungicide with B. bassiana , the Biological Index (BI) was calculated. This index classifies chemical compounds according to their toxic effects on fungi cultured in vitro on a solid‐poisoned medium (Silva, Quintela, Mascarin, Barrigossi, & Lião, ). The BIs were calculated using the B. bassiana colony mean vegetative growth (VG), sporulation (SP) and conidia germination (GR) percentages, as compared with the controls (Soares, Monteiro, Babosa, & Mochi, ), as follows:BI=47VG+43SP+10GR100where the BI defines the level of fungicide toxicity against the entomopathogenic fungus ( B. bassiana ) in vitro, and GR, VG and SP are the proportions of conidia germination, fungus vegetative growth and conidia numbers, respectively, of the fungicide treatments compared with the controls.…”
Section: Methodsmentioning
confidence: 99%
“…The insecticide spiromesifen did not affect the biological traits of I. javanica CG1282. The germination of conidia is the first step for the successful fungal infection on the host and the subsequent epizootic (Alizadeh, Samih, Khezri, & Riseh, 2007;Khalil, Shah, & Naeem, 1985), so the toxicity of insecticides on this biological trait must be firstly accounted in compatibility tests ( Faria, Hotchkiss, Hajek, & Wraight, 2010;Hirose et al, 2001;Neves, Hirose, Tchujo, & Moino, 2001;Silva et al, 2013). Likewise, Cuthbertson, Walters, and Deppe (2005), Cuthbertson et al (2008) Elbert, Fischer, & Tieman, 2003), which could impair the cellular immune system and facilitate fungal penetration and development.…”
Section: Discussionmentioning
confidence: 99%
“…Each treatment (i.e., mixture of fungal conidia + insecticide) was replicated four times (i.e., four independent tubes per treatment). To simulate a tank mixing of fungal conidia and pesticide, these mixtures were vigorously vortexed for 1 min and kept at constant agitation in a rotary shaker set to 25°C with 250 rpm for 2 hr prior to sampling (Silva, Quintela, Mascarin, Barrigossi, & Lião, 2013).…”
Section: In Vitro Compatibility Between Isaria Javanica and Chemicamentioning
confidence: 99%
“…Our management system (T 2 ) showed that a well-designed pest management program can control insect pests in an ecological manner (Bux et al, 2013;Ehi-Eromosele et al, 2013, improving overall environmental quality USEPA, 2015). Rodrigo et al (2013) reported that recommended insecticide application compatible with IPM practices are beneficial for the control of rice pests at any stage of crop.…”
Section: Discussionmentioning
confidence: 99%